2019
DOI: 10.1002/nop2.287
|View full text |Cite
|
Sign up to set email alerts
|

Families of patients in ICU: A Scoping review of their needs and satisfaction with care

Abstract: Aim To describe published literature on the needs and experiences of family members of adults admitted to intensive care and interventions to improve family satisfaction and psychological well‐being and health. Design Scoping review. Methods Several selective databases were searched. English‐language articles were retrieved, and data extracted on study design, sample size, sample characteristics and outcomes measured. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 51 publications
(187 reference statements)
2
43
0
11
Order By: Relevance
“…Thanks to their hope, family members can endure difficult times and still act as the situation requires (Verhaeghe et al, 2007). Eriksson (2018) It is already known (Scott, Thomson, & Shepherd, 2019;Wetzig & Mitchell, 2017;Wong et al, 2017) that family members feel a great need for information regarding the care of their loved ones and that uncertainty can arise when information is absent.…”
Section: Comprehensive Understanding and Reflectionsmentioning
confidence: 99%
“…Thanks to their hope, family members can endure difficult times and still act as the situation requires (Verhaeghe et al, 2007). Eriksson (2018) It is already known (Scott, Thomson, & Shepherd, 2019;Wetzig & Mitchell, 2017;Wong et al, 2017) that family members feel a great need for information regarding the care of their loved ones and that uncertainty can arise when information is absent.…”
Section: Comprehensive Understanding and Reflectionsmentioning
confidence: 99%
“…Data from the severe acute respiratory syndrome epidemic describe complex spiritual and psychosocial issues that can manifest [40]. COVID-19-related respiratory failure warranting long periods of ICU interventions such as prone positioning, paralysis, and sedation can result in post-intensive care syndrome and survivor's guilt [41,42].Even without the pandemic situation, family members of patients need to build a trusting alliance with the ICU team, failing which loss of confidence, and dissatisfaction ensues [43]. These family members tend to develop significant sleep disturbance, fatigue, and anxiety [44].…”
Section: Supportive Care Interventionsmentioning
confidence: 99%
“…Previous research has found that insufficient communication and lack of involvement in decision-making increases level of post-ICU anxiety and posttraumatic stress [9,19,24]. Satisfaction is higher in those families whose needs have been met, particularly in relation to communication and decision-making preferences [41][42][43]. Another study reported that nurse competency, concern and caring, completeness of information, and dissatisfaction with decision-making were independent predictors of dissatisfaction with ICU care [44].…”
Section: Discussionmentioning
confidence: 99%